(untitled) (Politeja, 2017)
Few subjects in the theory and practice of international relations are as sensitive and widely discussed as the meaning of sovereignty. Concentrating on transatlantic perspecive, this article adds new evidence to the fundamental debate on the nature of sovereign authority in the international system. Many trans‑national economic and technological forces encourage the state to retreat from its traditional role. On the other hand, economic integration, monetary unification and the development of modern economies and cutting‑edge technologies – the assets of partners of the Transatlantic Alliance – are possible only in stable political systems. So, are we witnessing the end of sovereignty or just a phase in history in which relations of power between political authorities, nations, groups of interests and individuals must be negotiated in order to create a new model of governa nce in a complex world?